2023
DOI: 10.3389/fcimb.2022.957512
|View full text |Cite
|
Sign up to set email alerts
|

Immunological aspects of host–pathogen crosstalk in the co-pathogenesis of diabetes and latent tuberculosis

Abstract: IntroductionDiabetes is a potent risk factor for the activation of latent tuberculosis and worsens the tuberculosis (TB) treatment outcome. The major reason for mortality and morbidity in diabetic patients is due to their increased susceptibility to TB. Thus, the study was conducted to understand the crosstalk between M. tuberculosis and its host upon latent tuberculosis infection and under hyperglycemic conditions or diabetes.MethodsAn animal model was employed to study the relationship between latent tubercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Verma et al established a latent TB infection mouse model and induced diabetes in Mtb-infected mice by administering streptozotocin to investigate the relationship between latent TB and diabetes. These hyperglycemic conditions led to a decrease in MCP-1 and MMP9 levels and increased MMP1 levels in latent TB infection, which may lead to reactivation of latent TB infection by disrupting granulomas (218). Clement et al reported that metabolic stress caused by hyperglycemia decreases Ag presentation ability and inhibits the proliferation of CD4 + T cells (219).…”
Section: Vaccine Application In the Context Of Underlying Diseasesmentioning
confidence: 99%
“…Verma et al established a latent TB infection mouse model and induced diabetes in Mtb-infected mice by administering streptozotocin to investigate the relationship between latent TB and diabetes. These hyperglycemic conditions led to a decrease in MCP-1 and MMP9 levels and increased MMP1 levels in latent TB infection, which may lead to reactivation of latent TB infection by disrupting granulomas (218). Clement et al reported that metabolic stress caused by hyperglycemia decreases Ag presentation ability and inhibits the proliferation of CD4 + T cells (219).…”
Section: Vaccine Application In the Context Of Underlying Diseasesmentioning
confidence: 99%